A generalization of Hermite interpolation - Xie-Hua Sun; Tingfan Xie (International Journal of Mathematics and Mathematical Sciences)
We introduce a new interpolation at Chebyshev nodes. The usual Hermite interpolation is the limit case of our new interpolation as h→0